Kerja Sama FLEGT-VPA (Forest Law Enforcement Government and Trade-Voluntary Partnership Agreement) Indonesia-Uni Eropa dalam Peningkatan Ekspor Produk Hasil Hutan Indonesia ke Uni Eropa - Kunkunrat Kunkunrat; Riska Putri Hariyadi (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2017)
Since the rate of forest destruction in the world continues to increase due to illegal logging, many international relations actors, both State and non-state actors encourage the creation of good forest governance. One of those involved in this mechanism is Indonesia and the Europe-Union. Both parties agreed on a voluntary cooperation scheme known as FLEGT-VPA. This study intends to see the correlation of forest management cooperation schemes with increasing export of Indonesian forest products to the EU. This is done because FLEGT-VPA cooperation is a cooperation related to forest governance, but in its implementation is very closely related to export activities. Moreover, Indonesia itself relies on the timber that is included in forest products as its pre-eminent commodities, therefore this research also tries to describe Indonesia's participation as a voluntary partner in FLEGT-VPA is inseparable from the motive of national interest in the economy.